PENINGKATAN KEPUASAN WALI MURID PADA LAYANAN PAUD MELALUI PRAKTEK MOTHERLY LEADERSHIP DI KB ABACA BUMIAYU - wiyani, novan ardy (IAIN Tulungagung, 2018)
This descriptive qualitative research is aimed to describe the efforts made by the head of KB ABACA Bumiayu to increase the satisfaction of the parents in early children education service through motherly leadership practice. The data in this research is collected by interview, observation, and documentation. The data has been collected and then analyzed using data analysis technique inductively. The results showed that basically the practice of motherly leadership by the head of KB ABACA Bumiayu is a lead way that focuses on providing early childhood services to meet the wishes, needs and expectations of guardians. Satisfaction will be gained by the guardians when their needs, desires, and expectations can be achieved. To be able to produce early childhood services that can satisfy the guardian, the head of KB ABACA actualize the four characters of a mother, namely trustworthy or trustworthy, responsible, diligent, and caring. Keywords: satisfaction, service, head of playgroup.